Late gadolinium enhancement patterns in severe symptomatic high-gradient aortic stenosis. (3rd October 2022) - Maltes, S; Abecasis, J; Santos, R R; Oliveira, L; Mendes, G S; Guerreiro, S; Lima, T; Freitas, P; Ferreira, A; Cardim, N; Gil, V M; Mendes, M
Abstract: Background: Left ventricular (LV) remodeling in patients with severe aortic valve stenosis (AS) is a complex process that goes beyond hypertrophic response and may involve reparative/replacement fibrosis. Currently, cardiac magnetic resonance (CMR) is the gold-standard imaging technique for detecting focal myocardial fibrosis through late gadolinium enhancement (LGE). However, myocardial fibrosis prevalence and distribution is quite variable among series. Our goal was to assess LGE prevalence and distribution pattern in severe symptomatic high-gradient AS. Methodology: Single-center prospective cohort of 132 patients with severe symptomatic high-gradient AS (mean age 73±11 years; 48% male, mean valvular transaortic gradient 60±20 mmHg; mean aortic valve area 0.7±0.2 cm 2 /m 2 ; mean LV ejection fraction by 2D echocardiogram 58±9%), all with normal flow (except one) undergoing surgical aortic valve replacement. Those with previous history of acute myocardial infarction, ischemic cardiomyopathy or other cardiomyopathy were excluded. All patients performed 1.5T CMR assessment with LV myocardium tissue characterization prior to surgery. Segmental LGE presence was assessed by two independent operators and classified according to the AHA 16 segment model, using 5-standard deviations from remote myocardium as the signal intensity cut-off for LGE identification and quantification. Results: Overall, 96 patients (74%) had non-ischemic LGE (median LGE mass 3.2 g [IQR 0.2–8.3] g; median percentage of LGE myocardial mass 2.5% [IQR 0.1–6.1]%); 22 patients [17%] with exclusively junctional LGE); in one patient an incidental ischemic scar (subendocardial distribution) was identified. No cases of subepicardial distribution were found. Intramyocardial LGE was most frequently observed in basal and mid-anterior and inferior interventricular septum – see Figure 1. In these segments, LGE was most often junctional at right-ventricular insertion points (54%), followed by mid-wall LGE (32%) or both sites involvement (14%). Conclusion: LGE is frequent in symptomatic high-gradient AS patients with preserved left ventricular ejection fraction, most often presenting as junctional enhancement in basal/mid-anterior and inferior interventricular septum. Future studies may address whether distinct LGE patterns may impact patient prognosis. Funding Acknowledgement: Type of funding sources: None.